A study on the effects of four reading methods on college students’ cognitive abilities and mental health based on positive psychology: taking Lao She’s works as an example - Liu, Yamei (Frontiers in Psychology, 2025)
BackgroundRising anxiety and depression among college students demand effective interventions. While reading benefits mental health, the comparative effects of different reading methods (paper, digital, audio, video) remain unclear.MethodsTwo thousand eight hundred sixty students were screened (SAS/SDS) and randomized into paper (PTR), digital (ETR), audio (ALR), video (VIR), or control groups. All groups read Lao She’s works with positive psychology themes for 8 weeks. Cognitive (CFQ, BRIEF-A) and mental health (SAS/SDS) outcomes were measured.ResultsPTR and ALR most effectively improved cognitive function (reduced CFQ scores) and mental health (lower anxiety/depression). ETR showed modest benefits, while VIR had minimal impact. The control group showed no improvement.ConclusionPaper and audio reading are optimal for enhancing cognition and mental health in students, offering practical guidance for evidence-based interventions.